Additive‐free, robust and superelastic dual‐network graphene/melamine composite sponge for motion sensing. Issue 32 (1st April 2021) - Zhang, Linjiong; Feng, Lianfang; Gu, Xueping; Zhang, Cailiang
Abstract: Graphene aerogel (GA) has a large potential in many fields such as energy storage, catalyst support, and sensors. However, its poor mechanical property has restricted the wide application. In this work, superelastic and robust melamine/graphene composite sponges are prepared by constructing a dual‐network structure of melamine and graphene without any chemical additives. The strength of as‐prepared composite sponge at 50% strain can reach 40 times higher than that of controlled GA. After 50 compressive cycles, the strain and strength recovery ratios of composite sponge are about 97% and 90%, respectively. More importantly, the excellent compression performance combines with the good electrical conductivity of the graphene network enable it as a dynamic piezo‐resistive material, which can provide immediate responses to dynamic stresses and strains with different frequencies. Benefitting by these excellent performances, the dual‐network composite sponge shows a great potential application in the field of motion sensing. Abstract : Superelastic and robust melamine/graphene composite sponges are prepared by constructing a dual‐network structure of melamine and graphene without any chemical additives. Excellent compression performance combines with the good electrical conductivity of the graphene network enable it as a dynamic piezo‐resistive material, which can provide immediate responses to dynamic stresses and strains with different frequencies.